Integration challenges for the deployment of a multi-stage zero-defect manufacturing architecture - Angione, Giacomo (2020)
Multi-stage manufacturing, typical in important industrial sectors, is inherently a complex process. The application of the zero-defect manufacturing (ZDM) philosophy, together with recent technological advances in Cyber-Physical Systems (CPS), presents significant challenges and opportunities for the implementation of new system architectures that contributes for the continuous improvement of the production. This paper describes the experience gained in the GO0D MAN project which aims at realizing a fully functional, replicable and therefore widely exploitable solution, employing multi-agent systems, smart on-line inspection tools, data analytics and knowledge management technologies. In particular, the paper presents the challenges tackled during the deployment of the GO0D MAN system architecture in three relevant industrial use cases, which represent more than 80% of the manufacturing sector.